1978
DOI: 10.1111/j.1469-8137.1978.tb01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Concentrations in Plants Responsible for Inhibition of Mycorrhizal Infection

Abstract: SUMMARYUsing a 'split root' technique, it was found that phosphorus fertilization of half of the root system of sudangrass could significantly reduce the number of chlamydospores of the mycorrhizal fungus Glomus fasciculatus in the unfertilized half of the root system. In a second experiment, vials of soil containing different concentrations of phosphorus were inserted into pots of sudangrass which were fertilized with different amounts of phosphorus and inoculated with G. fasciculatus. The numbers of chlamydo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
2
4

Year Published

1981
1981
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(134 citation statements)
references
References 9 publications
(5 reference statements)
7
119
2
4
Order By: Relevance
“…Mycorrhizal fungi added to fumigated, steamed, or autoclaved soils have been shown to increase growth of citrus up to 108.9% [16]. In the present study, plants inoculated with different AMF treatments in field soil grew better in general compared with noninoculated plants; however, the differences were significant at all intervals of observation only with T 4 where the most effective and infective inoculum was the mixed one and T 2 (Gigaspora gigantia) was least effective and infective at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal fungi added to fumigated, steamed, or autoclaved soils have been shown to increase growth of citrus up to 108.9% [16]. In the present study, plants inoculated with different AMF treatments in field soil grew better in general compared with noninoculated plants; however, the differences were significant at all intervals of observation only with T 4 where the most effective and infective inoculum was the mixed one and T 2 (Gigaspora gigantia) was least effective and infective at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Sanders (15) found that foliar application of P inhibited VAM infection of onion, demonstrating that P concentration within the host plays a more important role. Using a split-root technique, Menge et al (8) confirmed this finding when they established that the portion of the root system ' Abbreviation: VAM, vesicular-arbuscular mycorrhizae.…”
mentioning
confidence: 91%
“…Tiwari et al (1989) have found a higher effect of the inoculation of plants by P-solubilizing bacteria in soils deficient in available phosphorus. Many other authors (Menge et al 1978, Thomson et al 1986, Amijee et al 1989) demonstrated that the colonization of plant roots with VAM fungi was inhibited by higher mineral phosphate fertilization. In spite of many hypotheses, however, the mechanism of the colonization has not been yet sufficiently explained.…”
mentioning
confidence: 99%